An unusual mediastinal giant parathyroid adenoma: A rare case report - Ahmad Huneity; Yaman M. Alahmad; Issam Al Bozom; Abdelkareem Alhyari; Ayoub Alaoud; Rajendra Kumar (Radiology Case Reports)
Parathyroid adenoma is the most common cause of primary hyperparathyroidism. Giant parathyroid adenoma is considered a rare subtype of parathyroid adenomas that weigh more than 3.5 grams and cause a small number of adenoma related hyperparathyroidism. We present a case of 68-year-old asymptomatic male patient who had hypercalcemia and markedly high parathyroid hormone level on routine blood testing. Radiological investigations demonstrated a large mediastinal mass that showed peripheral high uptake on sestamibi scan. Histopathology confirmed the diagnosis of giant parathyroid adenoma. Giant parathyroid adenomas can have an atypical radiological appearance and present as a mediastinal mass that resembles other mediastinal masses, making it important to include in the list of possible diagnoses.